Heraldo Muñoz y Carlos Portales. UNA AMISTAD ESQUIVA: LAS RELACIONES DE ESTADOS UNIDOS Y CHILE, Pehuén, 1987, Santiago, 179 pp. - Meneses, Emilio (Revista de Ciencia Política, 2019)
Sin resumen disponible